THE EFFECT OF TRUST, PRICE, AND EASE OF TRANSACTION ON BUYING INTEREST AND THEIR IMPLICATIONS ON PURCHASE DECISIONS STUDY PT. INDONESIA MAYBANK FINANCE ONLINE CUSTOMER - Sundah, Felix; Tecoalu, Melitina; Wahyoedi, Soegeng (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2022)
This study aims to determine the impact or influence both directly and indirectly on a person's level of trust, the price offered and the ease of transacting with online or online services offered by PT. Maybank Indonesia Finance does it affect a person's buying interest and the implications for making online purchasing decisions. In this study, the methodological approach used was 94 respondents from Online / Online Customers of PT. Maybank Indonesia Finance which has become a customer of PT Maybank Indonesia Finance by using the Company's Digital platform in the acquisition process. Each respondent is given a related questionnaire related to the level of trust and buying interest. The price of buying interest, the ease of buying interest and buying interest have implications for purchasing decisions. The proposed hypothesis is tested, and its predictability is assessed through PLS -SEM. From the test results found findings that explain the direct relationship of price to purchase requests and the indirect relationship between price and influence on buying interest and its implications for purchasing decisions have a significant effect. While trust, ease of transacting directly has no effect on asking to buy and indirectly has no effect on asking to buy and its implications for purchasing decisions, while the direct relationship of buying interest with purchasing decisions has a very strong influence on online customers / Online PT. Maybank Indonesia Finance.